Making sense of loss, stress, resilience, empowerment, perception of resources, and health in grandparents raising grandchildren - Piper, Jessie L. (Kansas State University, 2020)
In 2012, 10% of children in the US lived with a grandparent, rising from 7% in 1992; 2.7 million grandparents were raising their grandchildren and about 39% of these grandparents had been doing so for 5 years or more. Although there are many benefits of grandchildren living with their grandparents (e.g., love, structure, safety, maintenance of connections), the events leading up to the transition are often traumatic and/or unanticipated, which compounded by the responsibilities of caregiving, can leave grandparents feeling loss and stress. In this study, family stress theory was used to explore the relationships between grandfamily demographics; various characteristics (e.g., length of caregiving, number and ages of grandchildren, etc.); their experience of loss, stress, resilience, and empowerment; their perceived informal supports and formal resources; and their overall health. Hypotheses were tested using multiple regression, hierarchical regression, and path analysis. Results indicate that age, marital status, rurality, custody arrangement, and parental involvement all might play a role in predicting stress, loss, empowerment, perceived informal resources, and perceived formal resources. Income and parental involvement might also play a role in predicting grandparent health before and while raising their grandchild(ren). The role of perception of informal resources as it relates to loss, stress, resiliency, and empowerment indicate that having personal supports, such as family and friends, is very important for grandparents raising grandchildren. Future research, utilizing this survey and other data collection methods, should continue to investigate these complex relationships and families.
Keywords: Grandfamily; Grandparents Raising Grandchildren; Family Stress Theory; Loss; Resources; Health